(untitled) (Universal International Scientific Journal, 2026)
This article examines the psychological aspects of school students’ cognitive development in the modern educational process. Cognitive development is considered as a process related to the formation and development of students’ cognitive processes such as sensation, perception, attention, memory, thinking, and imagination. The article highlights the influence of the educational environment, innovative pedagogical technologies, and teachers’ activities on students’ intellectual development. It also explains the importance of psychological factors in developing students’ independent thinking, problem-solving skills, and creative thinking. The results of the study show the importance of supporting students’ cognitive development and developing effective teaching strategies in the modern educational process.